2014
DOI: 10.1007/s00125-014-3194-z
|View full text |Cite
|
Sign up to set email alerts
|

TIAM1–RAC1 signalling axis-mediated activation of NADPH oxidase-2 initiates mitochondrial damage in the development of diabetic retinopathy

Abstract: The TIAM1-RAC1-NOX2 signalling axis is activated in the initial stages of diabetes to increase intracellular ROS leading to mitochondrial damage and accelerated capillary cell apoptosis. Strategies targeting TIAM1-RAC1 signalling could have the potential to halt the progression of diabetic retinopathy in the early stages of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
189
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 121 publications
(206 citation statements)
references
References 46 publications
11
189
0
Order By: Relevance
“…Consistent with our data, a previous report showed that ROS production and Nox2 expression were increased in the diabetic retina [3,22,35]. Glycyrrhizin has been shown to bind HMGB1 and inhibit its cytokine-like activities [27].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with our data, a previous report showed that ROS production and Nox2 expression were increased in the diabetic retina [3,22,35]. Glycyrrhizin has been shown to bind HMGB1 and inhibit its cytokine-like activities [27].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we demonstrated that HMGB1 expression was upregulated in the retinas of diabetic mice and rats [1,26] and that HMGB1 plays a key role in mediating diabetes-induced retinal vasculopathy and neuropathy [22,1,26]. Five key findings emerged from this study.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…94,96 In addition, recent studies from Sidarala and colleagues present the evidence that the Rac1-Nox2 signaling is vital in high glucose induced activation of stress activated kinases and loss in GSIS causing islet β-cell dysfunction. 97 Despite these in vitro evidences, potential roles for Nox in islet dysfunction in animal models of type 2 diabetes are minimal.…”
mentioning
confidence: 99%